국내산 사과의 품종별 Procyanidin B2, C1 함량 및 분석법 검증 - 김지영(Ji Yeong Kim); 장하나(Ha Na Jang); 김기창(Gi Chang Kim); 강해주(Hae Ju Kang); 황인국(In Guk Hwang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구에서는 사과의 주 기능 성분인 procyanidin B2와 C1의 정확성 있는 함량 분석을 실시하기 위해 분석법 검증을 실시하였으며 사과 품종(썸머킹, 부사, 감홍, 아리수, 홍로)과 부위(전체, 과육, 껍질) 그리고 농가 별 감홍 품종의 procyanidin B2, C1의 함량을 비교･분석하였다. 분석법 검증을 통해 procyanidin B2, C1의 피크가 다른 물질과의 간섭없이 분리되어 높은 직선성을 가짐을 확인 하였으며 검출한계는 각각 0.70, 0.77 µg/mL, 정량한계는 각각 2.14, 2.32 µg/mL로 나타났다. 또한 정밀성 분석을 위해 실시한 일내, 일간 분석과 정확성 분석을 위해 실시한 회수율 분석에서 모두 상대표준편차(RSD) 값이 5% 이내의 우수한 정밀성과 정확성이 있는 검증임을 확인하여 사과의 정량 분석 실험을 진행하였다. 품종별 함량 분석 결과 전반적으로 감홍 품종의 procyanidin 함량이 유의적으로 높고 아리수 품종이 낮은 함량을 보였으며 부위별 함량 분석을 통해 껍질 부위가 전체와 과육 부위보다 높은 함량을 나타냄을 확인할 수 있었다. 감홍 껍질의 procyanidin B2 함량이 14.84 mg/100 g FW를 나타내어 아리수 껍질보다 약 8배 높았으며 감홍 껍질의 procyanidin C1의 함량은 18.34 mg/100 g FW로 확인되어 다섯 품종의 껍질 평균 함량인 10.09 mg/100 g FW보다 월등히 높은 함량을 나타내었다. 농가로부터 수집한 감홍 품종의 전체, 과육, 껍질 부위별 procyanidin B2는 각 1.82 ~4.46, 1.28~3.34, 5.99~13.08 mg/100 g FW 함량을 보였으며 procyanidin C1은 각 2.22~4.48, 1.37~3.35, 8.42 ~15.49 mg/100 g FW 함량을 보여 농가 간의 함량 차이를 보였다. 이는 재배 품종, 재배 조건 등으로 인한 것으로 추정되었으며 국내에서 재배되는 사과 품종의 procyanidin 함량 정보를 정확히 구축하는 것은 사과의 기능 성분 함량 정보를 제공하고 나아가 사과의 이용성 증진 연구의 중요한 기초자료가 될 것으로 사료 된다. Procyanidin is a major functional component of apples. This study sought to verify an analytical method to evaluate the procyanidin B2 and C1 content by varieties, parts, and farms of apples. The linearity of the method developed using ultra performance liquid chromatography (UPLC) was excellent, and the correlation coefficients (R2) of procyanidin B2 and C1 were 0.9996 and 0.9996, respectively. The limits of detection of procyanidin B2 and C1 were 0.70 and 0.77 µg/mL and limits of quantification were 2.14 and 2.32 µg/mL, respectively. The relative standard deviation (RSD) of the intra-day and inter-day were calculated and had excellent precision and was found to be within 5%. The RSD of the recovery rate of procyanidin B2 and C1 were 0.68∼3.33% and 1.63∼2.78%, respectively. Through this, the analytical method for estimating procyanidin was confirmed. Analysis of procyanidin in the different apple varieties (Summerking, Gamhong, Hongro, Arisu, Busa), showed that Gamhong had significantly (P<0.05) higher procyanidin B2 and C1 content compared to other varieties, and the peel had the highest procyanidin B2 and C1 content. When the procyanidin content of Gamhong collected from ten farms was analyzed, the average content of procyanidin B2 in the peel was 9.79 mg/100 g FW and that of procyanidin C1 was 11.58 mg/100 g FW. Heretofore, information on the procyanidin content in apples grown in Korea was insufficient. Therefore, it is considered that the results of this study can be considered necessary to improve the usability of apples. KCI Citation Count: 2